Work Tenure and Marital Status as Determinants of Job Stress among Nurses in the Inpatient Ward of Hospital X in Kotamobagu - Henny Kaseger; Christien Gloria Tutu; Moh. Rizki Fauzan; Hairil Akbar; Fachry Rumaf; Sri Bunga Mawarni Paputungan (Jurnal EduHealth, 2025)
Nurses are the frontline of healthcare services and are highly vulnerable to work-related stress due to complex tasks and heavy responsibilities. This study aimed to analyze the relationship between work tenure and marital status with job stress among nurses in the inpatient ward of Hospital X in Kotamobagu. A quantitative study with a cross-sectional design and correlational analysis was conducted. The population consisted of 272 nurses, from which 73 respondents were selected using simple random sampling. Data were collected through a structured questionnaire covering three main variables: work tenure, marital status, and job stress. Univariate analysis was used to describe frequency distributions, and bivariate analysis using the Chi-Square test was applied to examine associations between independent and dependent variables. The findings showed that work tenure (p = 0.000) and marital status (p = 0.004) were significantly associated with nurses’ job stress. Nurses with longer work tenure (≥3 years) and those who were married were more likely to experience job stress. Emotional support, a healthy work environment, and adequate rest are essential to effectively manage job stress among nurses.